Are secondary school environments conducive for active play opportunities? An objective assessment across Australian secondary school playgrounds. Issue 1 (2nd January 2017) - Hyndman, Brendon; Chancellor, Barbara
ABSTRACT: The presence of school playground facilities has been reported to encourage active play, yet there is a paucity of research identifying the presence and quality of features within Australian secondary school playgrounds. The aim of this research study was to examine if secondary school playground environments are conducive for active play opportunities within the context of Australian secondary schools. A 44-item reliable and valid audit tool was employed to objectively assess the quality, quantity, presence of facilities and design of secondary school playground environments. It was revealed that fixed playground facilities, obstacle courses and coloured surface markings were largely absent. Findings revealed that secondary school playgrounds were more conducive for sporting opportunities than opportunities for active play and informal games. Understanding the secondary school playground environment options for active play opportunities is important for informing future, effective school interventions to facilitate positive health outcomes for Australian adolescents.